The post-Covid 19 world... State and globalization: an analytical study of challenges and opportunities - Chahrazed, Admam; Kechout, Abderrafik (Journal of Economic, Administrative and Legal Sciences, 2020)
This article aims to contribute in the different research discussions about the initial results of Covid-19 pandemic on the world, with investigating its possible implications for the state’s roles under globalization’s processes, which lead us to highlight the shortcomings of the state of offering a viable alternative for traditional state policies to deal with the urgent crises, and to push states to be inward looking, through pursuing various mechanisms of confrontation, different in forms, but the same in its core, since they are essentially based on individual efforts, away from arrangements of cooperation and integration.